JARINGAN SYARAF TIRUAN DENGAN ALGORITMA BACKPROPAGATION UNTUK MEMPREDIKSI NILAI UJIAN KOMPETENSI SISWA (STUDI KASUS SMKS JABAL RAHMAH STABAT) - Kiki Sri Handayani; Katen Lumbanbatu; Magdalena Simanjuntak (Jurnal Abdi Ilmu, 2021)
Competency testing is a process of assessment (assessment) both technical and non-technical through the collection of relevant evidence to determine whether a person is competent or not yet competent in a certain competency unit or job qualification. The implementation of the series of "tests" is basically to determine the level of knowledge, skills and personality of students. To find out the passing standards of student competence in facing exams, a method is needed to process the old student grade data to predict the value of students who will take the national exam, namely by using the artificial neural network method with Backpropagation, the results obtained are 0.55178871 with the number of squared errors. 0.004595309, then the result has reached the target, then the iteration stops.